Perceived school climate and delinquency among Chinese adolescents: A moderated mediation analysis of moral disengagement and effortful control. (September 2020) - Zhang, Jingyi; Li, Dongping; Ahemaitijiang, Nigela; Peng, Wenya; Zhai, Boyu; Wang, Yanhui
Highlights: Perceived school climate (PSC) was associated with adolescent delinquency. Moral disengagement partially mediated the relation between PSC and delinquency. The mediating pathway was not significant for adolescents high in effortful control. Abstract: Although scholarly interest in the association between perceived school climate and adolescent delinquency is growing, research on how and for whom perceived school climate relates to delinquency is underdeveloped. Based on social control theory and the general theory of crime, the present study established a moderated mediation model to examine whether moral disengagement would mediate the relationship between perceived school climate and delinquency and whether the mediation process would be moderated by effortful control. A total of 1529 Chinese adolescents ( M age = 14.74 years, SD = 1.48) from seven middle and high schools completed anonymous questionnaires on perceived school climate, moral disengagement, effortful control, and delinquency. After controlling for gender, age, and socioeconomic status, the results indicated that: (a) perceived school climate was negatively related to adolescent delinquency; (b) the relationship between perceived school climate and delinquency was partially mediated by adolescent moral disengagement; and (c) effortful control moderated the direct and indirect relationships between perceived school climate and adolescent delinquency, such that these relationships were only significant for adolescents with low levels of effortful control. These findings shed light on how and for whom perceived school climate is associated with adolescent delinquency, and they can inspire practitioners to pay attention to the interaction of social control (e.g., perceived school climate) and self-control (e.g., effortful control) when providing prevention and intervention.